Hereditary diffuse gastric cancer: predominance of multiple foci of signet ring cell carcinoma in distal stomach and transitional zone. Issue 6 (11th May 2004) - Charlton, A; Blair, V; Shaw, D; Parry, S; Guilford, P; Martin, I G
Abstract : Background and aims: Germline mutations in the CDH-1 /E-cadherin gene are, to date, the only known cause of hereditary diffuse gastric cancer (HDGC). While two recent series of prophylactic gastrectomy described microscopic foci of signet ring cell carcinoma in sample sections from 10 macroscopically normal stomachs, whole stomach phenotype has not been mapped. We aimed to describe the size and distribution of foci in relation to mucosal zones and anatomical location. Methods: Six patients (from three HDGC kindred) were referred for total gastrectomy via three different referral pathways. Following fixation, five stomachs were completely blocked and one extensively sampled. Histopathology was mapped to a mucosal photograph of each stomach, enabling precise localisation of carcinoma foci, benign pathology, and mucosal zones. Results: There were 4–318 microscopic foci of intramucosal signet ring cell adenocarcinoma in the six macroscopically normal stomachs (foci size 0.1–10 mm in diameter). The distal third of the stomach contained 48% of total foci (range 29–75%). The body-antral transitional zone occupied 7.7% of mucosal area (range 3.6–11.8) but had 37% of foci (range 10%–75%). The largest foci were found in the transitional zone and foci density was five times greater in the transitional zone than in body or antral type mucosa. Conclusions: In germline CDH-1 mutation carriers, multiple microscopic foci of intramucosal signet ring cell carcinoma show a predilection for the distal stomach and the body-antral transitional zone. Targeting the transitional zone would maximise the likelihood of finding foci in macroscopically normal gastrectomies, and particular attention should be paid to this area during endoscopy.